Synthesis of a hexasaccharide partial sequence of hyaluronan for click chemistry and more - Bantzi, Marina; Rigol, Stephan; Giannis, Athanassios (Beilstein Journal of Organic Chemistry, 2015)
In the present work, the synthesis of a hexasaccharide partial sequence of hyaluronan equipped with a terminal azido moiety is reported. This hexasaccharide can be used for the attachment on surfaces by means of click chemistry and after suitable deprotection for biophysical studies.
Keywords: azide; click chemistry; extracellular matrix; hexasaccharide; hyaluronan; multivalency

(untitled) - Kim, S.-H.; Turnbull, J.; Guimond, S. (J. Endocrinol., 2011)

(untitled) - Hynes, R. O. (Science, 2009)

(untitled) - Theocharis, A. D.; Gialeli, C.; Bouris, P.; Giannopoulou, E.; Skandalis, S. S.; Aletras, A. J.; Iozzo, R. V.; Karamanos, N. K. (FEBS J., 2014)

(untitled) - Gandhi, N. S.; Mancera, R. L. (Chem. Biol. Drug Des., 2008)

(untitled) - Meyer, K.; Palmer, J. W. (J. Biol. Chem., 1934)

(untitled) - Weissmann, B.; Meyer, K. (J. Am. Chem. Soc., 1954)

(untitled) - Balazs, E. A.; Laurent, T. C.; Jeanloz, R. W. (Biochem. J., 1986)

(untitled) - Fraser, J. R. E.; Laurent, T. C. (J. Intern. Med., 1997)

(untitled) - Vigetti, D.; Karousou, E.; Viola, M.; Deleonibus, S.; De Luca, G.; Passi, A. (Biochim. Biophys. Acta, 2014)

(untitled) - Chen, W. Y. J.; Abatangelo, G. (Wound Repair Regener., 1999)

(untitled) - Arpicco, S.; Lerda, C.; Pozza, E. D.; Costanzo, C.; Tsapis, N.; Stella, B.; Donadelli, M.; Dando, I.; Fattal, E.; Cattel, L.; Palmieri, M. (Eur. J. Pharm. Biopharm., 2013)

(untitled) - Eliaz, R. E.; Szoka, F. C. (Cancer Res., 2001)

(untitled) - Wang, H.; Tan, M.; Zhang, S.; Li, X.; Gao, J.; Zhang, D.; Hao, Y.; Gao, S.; Liu, J.; Lin, B. (Int. J. Mol. Sci., 2015)

(untitled) - Jeanloz, R. W.; Flowers, H. M. (J. Am. Chem. Soc., 1962)

(untitled) - Takanashi, S.; Hirasaka, Y.; Kawada, M.; Ishidate, M. (J. Am. Chem. Soc., 1962)

(untitled) - Slaghek, T.; Nakahara, Y.; Ogawa, T. (Tetrahedron Lett., 1992)

(untitled) - Slaghek, T. M.; Hyppönen, T. K.; Ogawa, T.; Kamerling, J. P.; Vliegenthart, J. F. G. (Tetrahedron Lett., 1993)

(untitled) - Blatter, G.; Jacquinet, J. C. (Carbohydr. Res., 1996)

(untitled) - Dinkelaar, J.; Codée, J. D. C.; van den Bos, L. J.; Overkleeft, H. S.; van der Marel, G. A. (J. Org. Chem., 2007)

(untitled) - Tully, S. E.; Mabon, R.; Gama, C. I.; Tsai, S. M.; Liu, X.; Hsieh-Wilson, L. C. (J. Am. Chem. Soc., 2004)

(untitled) - Walvoort, M. T. C.; Volbeda, A. G.; Reintjens, N. R. M.; van den Elst, H.; Plante, O. J.; Overkleeft, H. S.; van der Marel, G. A.; Codée, J. D. C. (Org. Lett., 2012)

(untitled) - Rigol, S.; Xia, L.; Giannis, A. (Bioorg. Med. Chem., 2013)

(untitled) - France, R. R.; Compton, R. G.; Davis, B. G.; Fairbanks, A. J.; Rees, N. V.; Wadhawan, J. D. (Org. Biomol. Chem., 2004)

(untitled) - Wang, Z.; Zhou, L.; El-Boubbou, K.; Ye, X.-s.; Huang, X. (J. Org. Chem., 2007)

(untitled) - Geng, Y.; Zhang, L.-H.; Ye, X.-S. (Tetrahedron, 2008)

(untitled) - Izumi, M.; Fukase, K.; Kusumoto, S. (Biosci., Biotechnol., Biochem., 2002)

(untitled) - Olah, G. A.; Nojima, M.; Kerekes, I. (Synthesis, 1973)

(untitled) - Schultz, M.; Kunz, H. (Tetrahedron: Asymmetry, 1993)

(untitled) - Murray, R. W.; Singh, M.; Rath, N. (J. Org. Chem., 1997)

(untitled) - Murray, R. W.; Singh, M. (Org. Synth., 1997)